Strengthening nursing, midwifery and allied health professional leadership in the UK – a realist evaluation. Issue 4 (19th August 2021) - Jackson, Carolyn; McBride, Tamsin; Manley, Kim; Dewar, Belinda; Young, Beverley; Ryan, Assumpta; Roberts, Debbie
Abstract : Purpose: This paper aims to share the findings of a realist evaluation study that set out to identify how to strengthen nursing, midwifery and allied health professions (NMAHP) leadership across all health-care contexts in the UK conducted between 2018 and 2019. The collaborative research team were from the Universities of Bangor, Ulster, the University of the West of Scotland and Canterbury Christ Church University. Design/methodology/approach: Realist evaluation and appreciative inquiry were used across three phases of the study. Phase 1 analysed the literature to generate tentative programme theories about what works, tested out in Phase 2 through a national social media Twitter chat and sense-making workshops to help refine the theories in Phase 3. Cross-cutting themes were synthesised into a leadership framework identifying the strategies that work for practitioners in a range of settings and professions based on the context, mechanism and output configuration of realist evaluation. Stakeholders contributed to the ongoing interrogation, analysis and synthesis of project outcomes. Findings: Five guiding lights of leadership, a metaphor for principles, were generated that enable and strengthen leadership across a range of contexts. – "The Light Between Us as interactions in our relationships", "Seeing People's Inner Light", "Kindling the Spark of light and keeping it glowing", "Lighting up the known and the yet to be known" and "Constellations of connected stars". Research limitations/implications: This study has illuminated the a-theoretical nature of the relationships between contexts, mechanisms and outcomes in the existing leadership literature. There is more scope to develop the tentative programme theories developed in this study with NMAHP leaders in a variety of different contexts. The outcomes of leadership research mostly focussed on staff outcomes and intermediate outcomes that are then linked to ultimate outcomes in both staff and patients (supplemental). More consideration needs to be given to the impact of leadership on patients, carers and their families. Practical implications: The study has developed additional important resources to enable NMAHP leaders to demonstrate their leadership impact in a range of contexts through the leadership impact self-assessment framework which can be used for 360 feedback in the workplace using the appreciative assessment and reflection tool. Social implications: Whilst policymakers note the increasing importance of leadership in facilitating the culture change needed to support health and care systems to adopt sustainable change at pace, there is still a prevailing focus on traditional approaches to individual leadership development as opposed to collective leadership across teams, services and systems. If this paper fails to understand how to transform leadership policy and education, then it will be impossible to support the workforce to adapt and flex to the increasingly complex contexts they are working in. This will serve to undermine system integration for health and social care if the capacity and capability for transformation are not attended to. Whilst there are ambitious global plans (WHO, 2015) to enable integrated services to be driven by citizen needs, there is still a considerable void in understanding how to authentically engage with people to ensure the transformation is driven by their needs as opposed to what the authors think they need. There is, therefore, a need for systems leaders with the full skillset required to enable integrated services across place-based systems, particularly clinicians who are able to break down barriers and silo working across boundaries through the credibility, leadership and facilitation expertise they provide. Originality/value: The realist evaluation with additional synthesis from key stakeholders has provided new knowledge about the principles of effective NMAHP leadership in health and social care, presented in such a way that facilitates the use of the five guiding lights to inform further practice, education, research and policy development.